Fabrication and characterisation of Ni-coated carbon fibre-reinforced alumina ceramic matrix composites using electrophoretic deposition - Kaya, C; Kaya, F; Boccaccini, AR; Chawla, KK (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
The present study explores the feasibility of fabricating Ni-coated carbon fibre-reinforced alumina ceramic matrix composites via a single-infiltration electrophoretic deposition (EPD) process perfor mcd in vacuum. The nano-size boehmite sol was seeded using nano-size delta -alumina powder in order to control the final sintered microstructure and then characterised using transmission electron microscopy, differential thermal and thermogravimetric analysis (DTA/TG) and X-ray disc centrifuge system (BI-XDC) in order to determine the sol microstructure, phase transformation temperatures and particle size (also degree of agglomeration), respectively. An EPD manufacturing cell for fabrication of Ni-coated carbon fibre reinforced alumina matrix composites was designed and experiments were conducted under vacuum (first time to date), resulting in full deposition of the sol material throughout the voids within/between the fibre tows. Composites with high green density (67% theoretical density) were produced using an applied voltage of 15 V d.c. and deposition time of 400 s. The sintered density after pressureless sintering at 1250 degreesC for 2 h was 91% theoretical density. Crack path propagation test showed that the metallic Ni coating was able to provide a weak interface, as an indenter induced crack within the alumina matrix was deflected and arrested at the Ni interface. (C) 2001 Acta Materialia Inc. Published by Elsevier Science Ltd. All rights reserved.
Keywords: electrophoretic deposition; composites; nickel; interface; microstructure; BOEHMITE SOL; ENHANCED DENSIFICATION; TRANSFORMATION; GELS; Materials Science; Metallurgy & Metallurgical Engineering